2020
DOI: 10.1353/asi.2020.0036
|View full text |Cite
|
Sign up to set email alerts
|

Angkor Borei and Protohistoric Trade Networks: A View from the Glass and Stone Bead Assemblage

Abstract: Angkor Borei, Cambodia was an important urban center related to the early first millennium C.E. polity known as Funan. Excavations in the protohistoric period Vat Komnou Cemetery site uncovered over 1300 glass and stone beads, which are important material indicators of trade. In this article, we review data from earlier studies and add new previously unpublished data on glass and stone beads from this collection as well as previously unpublished glass compositional analyses from the nearby site of Oc Eo, Vietn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Several unusual beads are similar to beads found largely in peninsular Thailand, such as those made with m-Na-Ca-Al glass, gold-glass beads, and faience and imitation agate beads, signifying a trade relationship with these communities or that they were part of the same trade network(s). The presence of numerous high alumina mineral soda glass beads in the cemetery matrix and upper layers indicate that people at this site maintained regional connections as bead exchange networks shifted in the early first millennium CE and exchange within the Mekong Interaction Sphere expanded (Carter et al 2021). had previously suggested the shift from potash to high alumina mineral soda glass took place between 200 BCE-200 CE, based on a lack of potash beads in cemetery layers at the site of Angkor Borei, Cambodia.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Several unusual beads are similar to beads found largely in peninsular Thailand, such as those made with m-Na-Ca-Al glass, gold-glass beads, and faience and imitation agate beads, signifying a trade relationship with these communities or that they were part of the same trade network(s). The presence of numerous high alumina mineral soda glass beads in the cemetery matrix and upper layers indicate that people at this site maintained regional connections as bead exchange networks shifted in the early first millennium CE and exchange within the Mekong Interaction Sphere expanded (Carter et al 2021). had previously suggested the shift from potash to high alumina mineral soda glass took place between 200 BCE-200 CE, based on a lack of potash beads in cemetery layers at the site of Angkor Borei, Cambodia.…”
Section: Discussionmentioning
confidence: 84%
“…Elsewhere on the Thai peninsula at the site of Phu Khao Thong, glass recipes show affinities with objects produced at the site of Arikamedu in South India . Studies of glass beads within mainland Southeast Asia have identified multiple intraregional exchange networks that linked different communities on the coasts and inland areas, and which shifted over time Carter et al 2021;Dussubieux and Bellina 2018). Through the identification of specific bead recipes, archaeologists are able to move beyond one-dimensional interpretations that recognize glass beads merely as objects that represent contact with India, and instead have identified diverse economic networks linking different parts of South Asia and Southeast Asia, as well as more closely examining how different types of beads circulated within internal exchange networks.…”
Section: Trade and Economic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinese written sources documented that the Funan dynasty was established by an Indian Brahmin named Kaundinya and a local princess named Soma 31 . Archaeological evidence from glass and stone beads recovered from the Mekong Delta and peninsular Thailand 32 and archaeobotanical remains 33 suggests the possibility of multi-ethnic residence in areas of Protohistoric MSEA whose populations engaged in maritime trade (e.g., Bellina 2014 34 ). Collectively, these data suggest some level of Indian cultural influence in the Mekong Delta in the 1 st -3 rd c. CE.…”
Section: Discussionmentioning
confidence: 99%